2018
DOI: 10.1039/c7cp06922g
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of bursty multiprotein target search kinetics on DNA by colocalisation

Abstract: Proteins are capable of locating specific targets on DNA by employing a facilitated diffusion process with intermittent 1D and 3D search steps. Gene colocalisation and coregulation-i.e. the spatial proximity of two communicating genes-is one factor capable of accelerating the target search process along the DNA. We perform Monte Carlo computer simulations and demonstrate the benefits of gene colocalisation for minimising the search time in a model DNA-protein system. We use a simple diffusion model to mimic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 140 publications
0
20
0
Order By: Relevance
“…Thus, gene expression and molecular signalling processes in cells are typically performed by passive diffusion 79 , as active transport would easily exceed the resources of a cell. The often extremely low concentrations of signalling molecules may be compensated by spatial proximity (geometry-control) 80 between the loci where the molecules are produced and where they are supposed to bind 8184 . For the QS scenario we here showed that excessive production of AIs may not lead to more reliable signalling and, thus, allows a similar housekeeping economy for the partaking cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, gene expression and molecular signalling processes in cells are typically performed by passive diffusion 79 , as active transport would easily exceed the resources of a cell. The often extremely low concentrations of signalling molecules may be compensated by spatial proximity (geometry-control) 80 between the loci where the molecules are produced and where they are supposed to bind 8184 . For the QS scenario we here showed that excessive production of AIs may not lead to more reliable signalling and, thus, allows a similar housekeeping economy for the partaking cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additional important aspects to study include different, potentially anisotropic dispersal, proliferation, and motility strategies of bacterial cells 8 , non-Fickian or anomalous diffusion of AI molecules 84 , as well as the diffusivity of AI molecules depending on local bacteria density (transport channels and porosity of a biofilm) 8,61,63 . Other biologically-relevant aspects should include stimulations of cell mortality (when local cell densities become too high to allow flows of nutrients and oxygen), disposal of poisonous metabolic/waste products, of the history of experiencing cell environments 36 , mimicking heterogeneous micro-scale structure of bacterial biofilms/colonies 9,10 , and QS mechanisms for multiple species of QS-signalling molecules (“interference”) 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Flanking DNA sequence around the target DNA site has also been found to modulate the search process by altering the funnel-shaped protein-DNA binding energy landscape (8). These multifaceted search mechanisms have been captured in vitro via different spectroscopic approaches (9)(10)(11)(12)(13), and also through in silico models and simulations (14)(15)(16)(17)(18)(19)(20)(21)(22)(23) at single molecule level. The in vivo condition is, however, entirely different due to the presence of an astounding concentration (∼100-300 mg/ml) of dissolved macromolecules (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a general framework of stochastic transcription has been built to address both the uncorrelated transcription events and bursting behaviors [14]. Besides, the bursting transcription is suggested to lead to protein localization to facilitate target search in the transcription regulation, according to another recent modeling work [15].…”
Section: Introductionmentioning
confidence: 99%